2013
DOI: 10.1542/peds.2013-0557
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Definitions of Urinary Tract Infections in Spina Bifida Patients: A Systematic Review

Abstract: OBJECTIVE: Urinary tract infections (UTIs) are a common source of morbidity among children with spina bifida (SB) and are a frequently reported outcome in studies of this patient population. However, the criteria for a diagnosis of UTI are often not stated. We evaluated the literature on SB patients for the criteria that authors use to define parameters in reporting UTI outcomes. METHODS:Embase and Medline were queried with the medical subject heading terms "spinal dysraphism," "myelomeningocele," "infection,"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 35 publications
0
48
0
2
Order By: Relevance
“…As a result of the heterogeneity in criteria used to diagnose UTI, a standardized definition of UTI in the neurogenic bladder population was proposed for use in research [10]. We adapted this definition but chose to use a colony-count of 50,000 cfu/mL rather than the 100,000 cfu/ mL in the initial definition, based on the American Academy of Pediatrics definition of UTI in which 50,000 cfu/mL is considered a clinically significant bacterial burden [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the heterogeneity in criteria used to diagnose UTI, a standardized definition of UTI in the neurogenic bladder population was proposed for use in research [10]. We adapted this definition but chose to use a colony-count of 50,000 cfu/mL rather than the 100,000 cfu/ mL in the initial definition, based on the American Academy of Pediatrics definition of UTI in which 50,000 cfu/mL is considered a clinically significant bacterial burden [15].…”
Section: Discussionmentioning
confidence: 99%
“…This definition of UTI is adapted from that published by Madden-Fuentes et al, with a modified colony-count of 50,000 cfu/mL for UTI rather than 100,000 cfu/mL included in the initial definition [10]. Patients who did not meet these criteria, but had a positive urine culture, were included in the UTC group.…”
Section: Methodsmentioning
confidence: 99%
“…These patients routinely perform clean intermittent catheterization, which, when correctly performed, may result in asymptomatic bacteruria (ABU) but serve to reduce the risk for symptomatic (febrile) recurrences (i.e pyelonephritis) [36, 37]. …”
Section: Uti Risk Factorsmentioning
confidence: 99%
“…No validated criteria exist to define UTI in this population. 17 In addition, the reason that the culture was obtained (eg, for clinical suspicion of UTI versus routine surveillance) was also not available, which could have served as a proxy measure for the presence or absence of clinical symptoms. However, our previous work has shown that pyuria alone is not a good predictor of UTI in children with neurogenic bladder, 7 suggesting that the presence of pyuria may be more related to the presence of a specific pathogen rather than indicative of an infectious state.…”
Section: Discussionmentioning
confidence: 99%